(untitled) - FAO (Rome, 1997)
This paper outlines and analyzes the current structure of the world white maize economy, with emphasis on production, utilization, trade and technology development. The paper also contains production projections to the year 2000 and discusses some of the major constaints to expanding white maize production to meet the potential growth in demand.
Keywords: corn